Help-Seeking to Cope With Experiences of Violence Among Women Living With HIV in Canada. (March 2022) - Gormley, Rebecca; Nicholson, Valerie; Parry, Rebeccah; Lee, Melanie; Webster, Kath; Sanchez, Margarite; Cardinal, Claudette; Li, Jenny; Wang, Lu; Balleny, Rosa; de Pokomandy, Alexandra; Loutfy, Mona; et al.
Using baseline data from a community-collaborative cohort of women living with HIV in Canada, we assessed the prevalence and correlates of help-seeking among 1, 057 women who reported experiencing violence in adulthood (≥16 years). After violence, 447 (42%) sought help, while 610 (58%) did not. Frequently accessed supports included health care providers ( n = 313, 70%), family/friends ( n = 244, 55%), and non-HIV community organizations ( n = 235, 53%). All accessed supports were perceived as helpful. Independent correlates of help-seeking included reporting a previous mental health diagnosis, a history of injection drug use, experiencing childhood violence, and experiencing sexism. We discuss considerations for better supporting women who experience violence.